2001
DOI: 10.1007/pl00000850
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic nitrate and nitrite transporters

Abstract: Nitrate transport is the key step controlling the amount of nitrate incorporated by the cells and subsequent of storage, reduction or export. Molecular, genetic and biochemical approaches to the study of eukaryotic nitrate/nitrite transporters allow an initial understanding of this step, which is much more complex and structured than previously suspected. At the plasma membrane level, two gene families, Nrt1 and Nrt2, account for high- and low-affinity nitrate transporters. Functionality of NRT1 from Arabidops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
94
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 70 publications
6
94
1
Order By: Relevance
“…Nitrate is reduced by nitrate reductase and nitrite reductase, and the resulting ammonium is usually assimilated by glutamine synthetase (GS) and glutamate synthase (GOGAT), which is known as the GS-GOGAT cycle (1). In land plants and green algal cells, the nitrate anion is imported into the cell by specific transporters (2), and reduced to nitrite by NAD(P)H-dependent nitrate reductase (NAR) in the cytosol. Nitrite is subsequently reduced to ammonium by ferredoxin-dependent nitrite reductase (NiR) in plastids.…”
mentioning
confidence: 99%
“…Nitrate is reduced by nitrate reductase and nitrite reductase, and the resulting ammonium is usually assimilated by glutamine synthetase (GS) and glutamate synthase (GOGAT), which is known as the GS-GOGAT cycle (1). In land plants and green algal cells, the nitrate anion is imported into the cell by specific transporters (2), and reduced to nitrite by NAD(P)H-dependent nitrate reductase (NAR) in the cytosol. Nitrite is subsequently reduced to ammonium by ferredoxin-dependent nitrite reductase (NiR) in plastids.…”
mentioning
confidence: 99%
“…NRT1 proteins have been demonstrated both biochemically and genetically to be lowaffinity nitrate transporters (although the Arabidopsis NRT1.1 appears to function in both low-affinity transport system and HATS) (3). Although they are unrelated to the NRT2 proteins at the nucleotide or amino acid sequence level, NRT1 proteins are predicted to be members of the MFS and share an overall structure and membrane topology with the NRT2 family (6)(7)(8). Significantly, inhibition of primary root growth in an Arabidopsis nrt1.1 mutant was observed even in the absence of nitrate, leading Guo et al (22) to suggest that NRT1.1 may contribute to growth ''in a way that goes beyond the simple uptake of nitrate,'' perhaps through developmental signaling.…”
Section: A Signaling Role For Arabididopsis Nrt21 and Other Putativementioning
confidence: 99%
“…NRT2 proteins are members of the major facilitator superfamily (MFS) of transporter and transporter-like proteins (5). Higher plant NRT2 proteins are predicted to be nitrate transporters based on their homology to the fungal nitrate transporter CRNA and on the changes in nitrate uptake kinetics observed in Arabidopsis plants with mutations in NRT2 genes (6)(7)(8). Direct studies of nitrate uptake kinetics in higher plants have revealed two distinct systems: the low-affinity transport system that is responsible for uptake when nitrate is plentiful (Ͼ1 mM) and the high-affinity transport system (HATS) that is able to scavenge nitrate from the soil at concentrations between 1 M and 1 mM.…”
mentioning
confidence: 99%
See 2 more Smart Citations